PENERAPAN TEKNIK PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR SOSIOLOGI PENDIDIKAN PADA MAHASISWA PGSD SEMESTER VI UNIVET BANTARA SUKOHARJO - Meidawati Suswandari; Moefty Mahendra; Munawir . (Universitas PGRI Semarang, 2015)
Abstract This class action research aims to determine the extent of Problem Solving Approach Can Improve Learning Outcomes of Sociology of Education in Student PGSD Univet Bantara Sukoharjo VI semester academic year 2014/2015. Results of action research shows that use of problem solving methods proven to improve learning outcomes Sociology of Education at the VI semester students PGSD even academic year 2014/2015. Improved learning outcomes sociology of education can be evidenced by the significant increase in prasiklus and each cycle. At this stage of prasiklus, the value of the average grade: 1). The number of students who declared successful in this study were students who obtain Prasiklus value ?óÔÇ??Ñ76 of 59 students, the first cycle a number of 86 students, and Cycle II a number of 101 students from the overall total of 112 students. 2). The number of students who otherwise have not been successful in this study were students who scored <74 of Prasiklus 53 students, the first cycle a number of 26 students, and a number of 11 students of the second cycle of the overall total of 112 students.Keywords : green school, awearness, responsibility